Peran Teknologi dalam Memfasilitasi Pembelajaran Inkuiri: Membangun Keterampilan Berpikir Siswa di Era Digital - Rizaldi Rizaldi; Meliana Meliana; Dela Magfira; Alya Nurul Amaliah; Nur Fitria Ardila; Nurjihan Ufairah Qadri (PT. Citra Media Publishing, 2025)
21st century education demands the development of students' critical thinking skills to face the challenges of the digital era. This article examines the role of technology in supporting inquiry learning as an innovative method that encourages active exploration and critical analysis. With a descriptive approach based on literature study, this research shows that technology integration can increase students' digital literacy, facilitate collaboration, and expand access to learning resources. However, the implementation of technology-based inquiry learning faces challenges, such as gaps in digital access and limited teacher skills. This article also discusses the advantages and disadvantages of inquiry learning strategies, as well as providing recommendations for optimizing their application in modern education. These findings are expected to provide practical insights for educators in maximizing learning in the digital era.